2021
DOI: 10.3390/jcm10040682
|View full text |Cite
|
Sign up to set email alerts
|

AN-VR-BE. A Randomized Controlled Trial for Reducing Fear of Gaining Weight and Other Eating Disorder Symptoms in Anorexia Nervosa through Virtual Reality-Based Body Exposure

Abstract: In vivo body exposure therapy is considered an effective and suitable intervention to help patients with anorexia nervosa (AN) reduce their body image disturbances (BIDs). However, these interventions have notable limitations and cannot effectively reproduce certain fears usually found in AN, such as the fear of gaining weight (FGW). The latest developments in virtual reality (VR) technology and embodiment-based procedures could overcome these limitations and allow AN patients to confront their FGW and BIDs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 86 publications
(125 reference statements)
5
89
0
Order By: Relevance
“…For example, Nameth et al [ 50 ] have shown that virtual reality can be used to deliver cue exposure among patients who binge. Similarly, Porras-Garcia et al [ 51 ▪ ] have demonstrated that virtual reality body exposure has positive effects on body image.…”
Section: Development Of Therapeutic Methods In Cognitive-behavioural Therapy For Eating Disordersmentioning
confidence: 96%
“…For example, Nameth et al [ 50 ] have shown that virtual reality can be used to deliver cue exposure among patients who binge. Similarly, Porras-Garcia et al [ 51 ▪ ] have demonstrated that virtual reality body exposure has positive effects on body image.…”
Section: Development Of Therapeutic Methods In Cognitive-behavioural Therapy For Eating Disordersmentioning
confidence: 96%
“…Assuming an alpha of 0.05 and a power of 0.80 (β−1) in a two-way repeated measure analysis of variance, a minimum of 27 participants would be required per study arm (three treatment conditions × four assessment factors). Allowing for a dropout rate of 20% of study participants from baseline, taking the average score of similar previous studies evaluating VR interventions, [17][18][19] a total of 96 participants need to be recruited.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Such characteristics indicate that ED and non-ED populations may show differences involving the multisensory integration processes underlying embodiment illusions and self-perception more broadly, as explained according to the previously outlined predictive coding theory [10,11]. As indicated in Table 3, researchers have begun to employ the classic embodiment and tactile-reduced paradigms to study the extent to which embodiment illusions occur in ED patients (e.g., [1,2,9,[27][28][29][30][31]).…”
Section: Embodiment Illusions In Eating Disorder Patientsmentioning
confidence: 99%
“…According to our search of the literature for such studies involving ED participants, there are at least seven studies that have been published since 2014 (the details of these studies are provided in Table 3; [2,[27][28][29][38][39][40]). Encouragingly, six out of these seven studies have reported evidence for improvements involving image related concerns (usually as indicated via reduced size over-estimations).…”
Section: Embodiment Illusions In Eating Disorder Patientsmentioning
confidence: 99%